The Effect of Work-Life Balance and Job Satisfaction on the Loyalty of Gen Z Employees in North Toraja Regency - Ellyn Patadungan; Marniati Marniati; Fhany Octavia (International Journal of Economics and Management Research, 2026)
Demographic changes in today’s workforce show an increasing proportion of Generation Z employees, born between 1997 and 2012. Gen-Z employees value work-life balance, flexibility, and meaningful work, but are often perceived as less loyal due to their tendency to change jobs easily. They view work as non-essential, especially when it does not meet their expectations for job satisfaction. When their needs are unmet, they are more likely to seek new opportunities. In North Toraja, understanding the factors that influence Gen-Z loyalty is crucial for managing and retaining young talent. This study examines the impact of work-life balance and job satisfaction on the loyalty of Gen-Z employees in North Toraja Regency. A questionnaire was distributed to 100 Gen-Z employees in the region. Descriptive and verification analysis were used to analyze the data. The findings indicate that work-life balance does not significantly affect employee loyalty, while job satisfaction has a significant influence. Additionally, the simultaneous test shows that both work-life balance and job satisfaction together affect the loyalty of Gen-Z employees in North Toraja Regency.